The Role of the State in Recognising the Customary Rights of Indigenous Peoples - Yustihasana Untoro, Utami; Konny Umboh, Nova; Agusta Fahlevie, Rinaldi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
This research evaluates the role of the state in recognising the customary rights of indigenous peoples. The issue at hand is conflict between indigenous peoples, private companies and individuals over the utilisation of customary land for various purposes. The focus of this research is a legal analysis of the role of state institutions in supporting the recognition and protection of customary rights of indigenous peoples. This research also aims to explain the relevance and purpose of state regulation in the recognition of indigenous peoples' customary rights in Indonesia, identify and analyse the problems faced by indigenous peoples' customary rights in Indonesia, even though normatively these rights have been recognised by the state and develop solutions for the fulfilment of indigenous peoples' customary rights in Indonesia by collaborating relevant theories.The type of research used is normative juridical, with an approach that involves the study of theories and concepts as well as research into legislation relevant to the topic. The results show that existing regulations are adequate, and the state is committed to recognising and protecting the rights of indigenous peoples. However, effective implementation still requires a more collaborative approach to overcome various obstacles.